2019
DOI: 10.1101/736975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role of oligodendrocytes in information processing independent of conduction velocity

Abstract: 41Myelinating oligodendrocytes enable fast impulse propagation along axons as revealed 42 through studies of homogeneously myelinated white matter tracts. However, gray matter 43 myelination patterns are different, with sparsely myelinated sections leaving large 44 portions of the axons naked. The consequences of this patchy myelination for 45 oligodendrocyte function are not understood but suggest other roles in information 46 processing beyond the regulation of axonal conduction velocity. Here, we analyze… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
2
6
0
Order By: Relevance
“…Longer latencies from wave II found in our mutant model reflect desynchronization of the input at central auditory pathways and nuclei (Roncagliolo et al, 2000). The same results were found in other models of demyelination (Moore et al, 2019). Normal wave I, both in our patient and in the tubulin mutant taiep rat, as well as the comparable thresholds between the tubulin mutant and controls, can be explained by the integrity of the inner ear, which we corroborated by morphology and normal DPOAEs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Longer latencies from wave II found in our mutant model reflect desynchronization of the input at central auditory pathways and nuclei (Roncagliolo et al, 2000). The same results were found in other models of demyelination (Moore et al, 2019). Normal wave I, both in our patient and in the tubulin mutant taiep rat, as well as the comparable thresholds between the tubulin mutant and controls, can be explained by the integrity of the inner ear, which we corroborated by morphology and normal DPOAEs.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, an additional function of oligodendrocytes is the metabolic support of myelinated axons (Moore et al, 2019). This role becomes even more important when axons spike at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…While both astrocytes and oligodendrocytes display projections from their cell bodies, those from oligodendrocytes specifically construct the myelin sheath around nearby neurons, a concentric wrapping that improves neuron repolarization and conduction speeds. Additionally, recent literature has demonstrated that oligodendrocyte myelination is not only distinct to single groups of neurons but also exhibits control over synaptic activity and can even manipulate information processing [ 45 , 46 , 47 ]. Microglia are the resident innate immune cells in the CNS, responding to pathogens and injury and clearing dead cells.…”
Section: Introductionmentioning
confidence: 99%
“…Newly added myelin sheaths could further provide metabolic support to axons (Fünfschilling et al, 2012;Meyer et al, 2018), the metabolic supply being regulated by neuronal activity (Saab et al, 2016). This myelin addition probably would not result in a global energetic advantage (Harris and Attwell, 2012), but might be needed to generate fast-spiking firing discharges and thus allow for precise axonal firing (Micheva et al, 2016;Moore et al, 2019).…”
Section: Myelination In Adulthood As An Adaptive Mechanismmentioning
confidence: 99%